Contrast Enhanced Ultrasound (CEUS) Characterization of Grey-scale Sonographic Indeterminate Focal Liver Lesions in Pediatric Practice - Jacob, J.; Deganello, A.; Sellars, M. E.; Hadzic, N.; Sidhu, P. S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To determine the usefulness of contrast-enhanced ultrasound (CEUS) in characterizing grey-scale sonographic indeterminate focal liver lesions (FLL) in pediatric practice.Materials and Methods: Local Ethics Board approval waiver was attained. Consent for CEUS examinations was acquired from parents. Forty-four children referred for CEUS assessment of grey-scale sonographic indeterminate FLL over a 5-year period underwent standard multiphase CEUS performed by experienced operators. A phospholipid microbubble agent was used and low mechanical index ultrasound imaging techniques employed. Interpretation by consensus of the CEUS examination was compared to consensus interpretation of other imaging and to histology. Follow-up imaging was used to confirm stability of benign abnormalities. Any contrast reactions were recorded.Results: The CEUS examination interpretation agreed with reference imaging in 29/34 (85.3 %) of cases. In discordant cases, reference imaging showed no abnormality (n = 5), with fatty change (n = 4) and regenerating nodules (n = 1) on CEUS and follow-up sonography. Where reference imaging was not performed (n = 10), histology (n = 7) or follow-up sonography (n = 3) confirmed the diagnosis. In one discordant case, all imaging modalities showed concordance identifying a malignant lesion; however histology demonstrated a benign hepatocellular adenoma. The specificity was 98.0 % (95 % CI; 86 – 100 %) and the negative predictive value was 100 %. No adverse effects to the contrast material were noted.Conclusion: These findings demonstrate the usefulness of CEUS in characterizing indeterminate grey-scale sonography FLL in pediatric patients with the potential to reduce exposure to ionizing radiation.
Keywords: ultrasonography; contrast media; liver; neoplasms; paediatrics